The Role of Technology in the Implementation of the Blended Learning Model - Lestari, Adek Ayu; Astuti, Devy Tri; Latif, Muhammad Aji; Andikos, Adi Fitra (The Future of Education Journal, 2024)
This research aims to describe the application of the Blended Learning model and its effect on students. Blended Learning integrates face-to-face learning with online technology, creating flexibility and effectiveness in the learning process. The method used is a Systematic Literature Review (SLR) of 10 selected articles from various sources that discuss the implementation of Blended Learning in elementary schools. The research results show that this model has a positive impact, such as increasing students' motivation, learning outcomes, critical thinking abilities and technology skills. Despite facing challenges such as student engagement in online learning, Blended Learning remains a promising approach to creating education that is relevant to the demands of the times. This model also encourages teachers to continue to innovate, create interesting learning, and motivate students to learn actively.